Use of Lactoferrin in the Treatment of Patients with Severe Concomitant Injury - V. M. Kapitonov; D. A. Ostapchenko; Ye. R. Nemtsova (Общая реаниматология, 2009)
Objective: to define the degree of activation of lipid peroxidation in patients with severe concomitant injury and to determine whether they could be corrected with the antioxidant agent Laprot. Subjects and methods. The time course of changes in lipid peroxidation parameters and clinical data was studied in 68 patients with severe concomitant injury, in 35 of whom Laprot (made by P. A. Herzen Moscow Oncological Research Institute, Russian Agency for Medical Technologies (Russia), was added to the standard treatment. Results. The significant activation of oxidative processes and lipid peroxi-dation, which was accompanied by antioxidant system imbalance, was ascertained to occur in severe concomitant injury. Key words: injury, lipid peroxidation, lactoferrin.